Sensemaking for writing programs and writing centers - Malenczyk, Rita, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
In this collection, writing program and writing center administrators from a range of academic institutions come together to explore their work through the lens of sensemaking. Sensemaking is an organizational theory concept that enables institutions, supervisors, teachers, tutors, and others to better understand the work they do using theoretical lenses.--Provided by publisher.
The medachtic tutor: Jewish discourse, metaphor, and undergraduate tutors' sensemaking of writing center work / Andrea Rosso Efthymiou -- Beyond the anecdote: TA sensemaking as writing program underlife / Courtney Adams Wooten -- Celebrating sensemaking cultures in the writing center: scaffolding transparent communication between tutors and directors / Jeanne R. Smith, Shannon McKeehen, Barbara George, and Yvonne R. Lee -- Tutor-to-tutor: attending to the operations of race and privilege among writing center staff members / Alba Newmann Holmes -- Making sense of how things feel: attending to emotional experiences in writing programs / Bronwyn T. Williams -- New writing center ecologies: challenging inherited sensemaking in the center / Genie Nicole Giaimo and Joseph Cheatle -- Stories to support and sustain a program: connections among the library, WID, and the writing center / Susanmarie Harrington and Sue Dinitz -- Cascading texts and cat's cradles: an institutional ethnographic approach to understanding the textual production of unionized labor / Melissa Nicolas -- Distributed leadership for WPAs: making sense of leadership methods / Christy I. Wenger -- Sensemaking as antiracist writing program administration: reappropriating activity and actor-network theory / Brian Hendrickson -- Afterword: a 2x2 review of sensemaking for writing programs and writing centers / Karen Keaton Jackson.
Keywords: Writing centers -- Administration; Writing centers -- Sociological aspects; English language -- Rhetoric -- Study and teaching (Higher); Tutors and tutoring